Causes and Consequences of Mixed-Species Coveys of California and Gambel’s Quail and Their Hybrids - Jennifer Gee (National Quail Symposium Proceedings, 2017)
California (Callipepla californica) and Gambel’s quail (C. gambelii) hybridize where their distributions overlap. Outside of the area of overlap, pairs are known to form within the covey. I observed two mixed-species coveys within the hybrid zone and examined if pairing occurred within the coveys. I compared hatching success and survival of chicks between resident within-covey pairs to immigrant pairs. Isolated coveys could become inbred, given that choice of conspecific mate may be constrained by small population size. I measured relatedness between quail for each individual that paired within the covey, and tested whether it was more or less related to its mate than to other individuals in the covey of the same and opposite sex. The hybrid zone between C. californica and C. gambelii appears to be bounded by ecological forces rather than genetic incompatibility. Clinal allelic and plumage trait differences between C. californica and C. gambelii map closely into the ecotonal area of hybridization. Quail species have fluid geographical distributions but extraordinarily plastic mating systems. This dynamic may help explain why quail have a higher incidence of hybridization than most other bird species.
Keywords: California quail; Callipepla californica; C. gambelii; Gambel’s quail; hybridization